Radikal ve Ilımlı Aydınlanma Düşüncesi Bağlamında Candide ile Pisagor'un Seyahatleri'nin Karşılaştırmalı İncelemesi. - MORKOÇ, Hasan (Journal of Faculty of Letters / Edebiyat Fakultesi Dergisi)
This study offers a comparative analysis of Candide (1759) by Voltaire and The Travels of Pythagoras (1799) by Sylvain Maréchal, focusing on the Enlightenment's central concepts of "reason," "religion," and "utopia." Drawing on the theoretical frameworks of Ruth Levitas, Jonathan Israel, and Bronisław Baczko, it distinguishes between the "moderate" and "radical" strands of Enlightenment thought and situates both works within this ideological spectrum. Candide critiques metaphysical optimism and religious fanaticism through an ironic narrative, while the "Eldorado" episode presents an unattainable and temporary model of an ideal society; ultimately, the work proposes a limited life practice grounded in reason, experience, and labor on an individual scale. This approach reflects Voltaire's moderate Enlightenment stance, characterized by cautious and pragmatic utopianism. In contrast, The Travels of Pythagoras employs the fictional journeys of an ancient sage to articulate a critique of institutional religion, advocate for social equality, and envision an atheist social order. Maréchal, in line with the radical Enlightenment tradition, advances ambitious goals such as the abolition of private property, the adoption of communal living, and the establishment of absolute equality, framing them within a utopian vision. The comparative evaluation reveals that Voltaire's critical yet reformist perspective and Maréchal's revolutionary and transformative approach represent the ideological diversity within Enlightenment literature. In this context, the study aims to make visible the internal differentiations of Enlightenment thought through literary texts and to discuss, within a historical framework, the role of utopian narratives as instruments of social and political critique.